Konsep kurikulum adab perspektif Syeikh Bakr Bin Abdullah Abu Zaid - Al-Kattani, Abdul Hayyie; Bahrudin, Bahrudin (TAWAZUN: Jurnal Pendidikan Islam, 2022)
This research was formulated to describe the Adab Curriculum persfectif Sheikh Bakr bin Abdullah Abu Zaid. This research is a type of qualitative research with a character study approach that aims to conduct an in-depth study of the thoughts of the figures studied. The study is conducted by the library reaserch method of primary literature and skunder relating to the object in question. In this study it was found sheikh Bakr explained the concept of adab curriculum. According to him, the adab curriculum is divided into three parts of the discussion, namely as follows: First, the discussion of the definition of adab curriculum, Second, what foundation is underlying, then the third is what components are contained in the adab curriculum itself. Implicitly Sheikh Bakr defines the adab curriculum as the arrangement of material received, taken, and passed by learners to obtain the values of knowledge, attitude and skills that are in accordance with the foundation of the Qur'an, al-Hadith, and ijtihad ulama. These three aspects are formulated into the womb of Islamic Education. The supporting program for the achievement of the adab curriculum delivered in the womb of Islamic Education is the objective of the curriculum is clearly targeted, the content / material taught according to the target, the methods used in the teaching is on target, and the evaluation in the curriculum is organized according to the target achievement. These four supporting programs are components in the curriculum of the book of Hilyah Thalibil 'ilm by Syeihk Bakr.AbstrakPenelitian ini dirumuskan untuk mendeskripsikan Kurikulum Adab perspektif Syeikh Bakr bin Abdullah Abu Zaid. Penelitian ini merupakan jenis penelitian kualitatif dengan pendekatan studi tokoh yang bertujuan untuk melakukan pengkajian mendalam terhadap pemikiran tokoh yang diteliti. Pengkajian dilakukan dengan metode library reaserch terhadap literatur primer dan skunder yang berkaitan dengan objek yang dimaksud. Dalam kajian ini ditemukan Syeikh Bakr memaparkan konsep kurikulum adab. Menurut beliau, kurikulum adab itu terbagi ke dalam tiga bagian pembahasan, yaitu sebagai berikut: Pertama, pembahasan tentang definisi kurikulum adab, Kedua, landasan apa saja yang mendasarinya, kemudian yang ketiga adalah komponen-komponen apa saja yang terdapat di dalam kurikulum adab itu sendiri. Secara implisit Syeikh Bakr mendefinisikan kurikulum adab merupakan susunan materi yang diterima, ditempuh, dan dilalui oleh peserta didik untuk memperoleh nilai-nilai pengetahuan, sikap dan keterampilan yang sesuai dengan landasan Alquran, al-hadits, serta ijtihad ulama. Ketiga aspek ini diformulasikan ke dalam rahim Pendidikan Islam. Program penunjang tercapainya kurikulum adab yang disampaikan dalam rahim Pendidikan Islam ialah tujuan kurikulumnya jelas sasaran, Isi/materi yang diajarkan sesuai sasaran, metode yang digunakan dalam pengajarannya tepat sasaran, serta evaluasi dalam kurikulumnya terorganisir sesuai target capaian. Keempat program penunjang ini merupakan komponen dalam kurikulum adab perspektif kitab Hilyah Thalibil ‘ilm karangan Syeihk Bakr.